2004
DOI: 10.1007/s00296-004-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of sacroiliitis with different imaging techniques in spondyloarthropathies

Abstract: Magnetic resonance imaging is the most sensitive method for detecting acute or chronic changes in SpA patients with histories of inflammatory low back pain and normal or indeterminate findings on plain radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Heuft-Dorenborsch et al found that initial assessment of structural changes by radiography followed by MRI assessment of inflammation with negative radiography gives the highest returns for detecting involvement of the SI joint in patients with recent IBP 27. Finally, two studies found MRI of the SI joint superior to QSS or radiography for diagnosing sacroiliitis in IBP and SpA 14 33…”
Section: Resultsmentioning
confidence: 99%
“…Heuft-Dorenborsch et al found that initial assessment of structural changes by radiography followed by MRI assessment of inflammation with negative radiography gives the highest returns for detecting involvement of the SI joint in patients with recent IBP 27. Finally, two studies found MRI of the SI joint superior to QSS or radiography for diagnosing sacroiliitis in IBP and SpA 14 33…”
Section: Resultsmentioning
confidence: 99%
“…In 12 these 23 studies the cut-off was even more precisely defined by calculating the mean radiotracer uptake in controls plus twice the standard deviation,24 28 34 3644 here the mean tracer uptake was 1.48 (SD 0.18). Two studies even used different age groups to define reference values 42 45…”
Section: Resultsmentioning
confidence: 99%
“…In two studies including a total of 37 patients with AS35 45 the pooled sensitivity of scintigraphy to detect acute sacroiliitis was 59.5% (22 of 37) compared with MRI as a gold standard (fig 3). Jee et al 35 found that of 11 patients with AS with a positive MRI six patients with AS also had a positive scintigraphy, here a κ value (for the comparison of scintigraphy and MRI) of 0.33 could be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Recognition of SI on radiographs of the sacroiliac joints is difficult and requires experience. Many studies have addressed the inter‐ and intra‐observer variability of this technique and CT and MRI scans have proven to be more sensitive and specific 3,15–17,41 . Nevertheless, due to the limited availability, high radiation exposure and/or relative high cost of these techniques, plain sacroiliac radiographs remain the initial diagnostic tool 11,18 .…”
Section: Discussionmentioning
confidence: 99%